2012
DOI: 10.1603/ec11322
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental and Physical Factors on Capture of Tribolium castaneum (Coleoptera: Tenebrionidae) in a Flour Mill

Abstract: Variation in environmental and physical factors within food processing facilities can influence both the distribution of stored-product pests and trapping efficiency. Data from a long-term Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) monitoring program was used to evaluate spatial variation in captures among trap locations and to determine relationships with environmental and physical variables. From the complete monitoring data set, different subsets were created for the cool and warm seasons, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Most trap locations were highly variable in terms of the number of moth captured over time, with the result that it was difficult to identify specific locations where monitoring should be focused. This could be the result of movement of infested material into and out of the warehouse, although a similar pattern was observed for Tribolium castaneum (Herbst), the red flour beetle, in flour mills (Semeao et al, 2012). In both cases, it may be that the high mobility of the adult insects is covering up the actual dispersion of the infestations.…”
Section: Yearmentioning
confidence: 63%
See 1 more Smart Citation
“…Most trap locations were highly variable in terms of the number of moth captured over time, with the result that it was difficult to identify specific locations where monitoring should be focused. This could be the result of movement of infested material into and out of the warehouse, although a similar pattern was observed for Tribolium castaneum (Herbst), the red flour beetle, in flour mills (Semeao et al, 2012). In both cases, it may be that the high mobility of the adult insects is covering up the actual dispersion of the infestations.…”
Section: Yearmentioning
confidence: 63%
“…However, the greater levels of capture inside, a trend for captures near doors not to be greater than in the warehouse interior, and observation of infested product suggests that at this location a resident population within the warehouse was of primary importance. Interpretation of pheromone trap catch data of stored product insects in relation to actual population density is confounded for a number of reasons including trap density, internal air movement, height of traps, age of pheromone lures, temperature and insect movement patterns (Campbell et al, 2002;Nansen et al, , 2008Trematerra and Gentile, 2010;Semeao et al, 2012), which ultimately affects adoption of monitoring programs and management strategies. Arbogast et al (2000) described two approaches for interpretation of trap catch data: representative, which assumes trap catch is a proportion of the total population, and indicative, which assumes trap catch as an indication of risk or a necessary management action.…”
Section: Yearmentioning
confidence: 99%
“…For walking T. castaneum, landscape features such as vertical edges have been shown to influence behavior (Campbell and Hagstrum, 2002). Semeao et al (2012) measured physical and environmental features associated with trap locations and their relationship with T. castaneum captures in a commercial flour mill. Variation in captures among locations and a significant relationship between insect capture and flour dust accumulation was found.…”
Section: Discussionmentioning
confidence: 99%
“…How T. castaneum respond to commercially available traps and attractants may be influenced by the landscape of physical and environmental conditions at the locations where traps are placed inside a food facility. Semeao et al (2012) found that trap locations within a flour mill with larger captures tended to have greater flour dust accumulation, higher temperatures, and closer proximity to milling equipment. Romero et al (2009) found that T. castaneum movement patterns were influenced by the distribution pattern of flour accumulations.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation